Kasanzu Lusasula..Appe Vs Lugito..Respo Civil Appe No.26 Of 2015 - Hon. Massati,J.A; Hon. Mussa, J. A.; Hon. Mwarija, J. A (High Court Tabora-Tanzania, 2024)
Appeal from the Judgment of the High Court of Tanzania, at Tabora NO. 26 of 2015